Ground Water-Bottom Soil-Water Interactions in Tropical Carp Nursery Ponds. - Habib, M.Ahsan; Alam, M.Jahangir; Rahman Khan, L; Begum, Momtaz (1991)
There was no significant combined effect (P > 0.05) of the physico-chemical properties of the underground deep tube well water on increasing the nutrient contents of the nursery ponds' bottom soil. But the combined effect of seven chemical properties of bottom soil showed significant (P < 0.05) influence on increasing the amount of chemical constituents of pond water except pH and exchangeable K. Electric conductivity, pH and exchangeable Ca of deep tube well water had inverse correlations with chemical properties of pond bottom soil but only dissolved O2 was directly correlated with all the properties of pond bottom soil. All the correlation values between pH and chemical properties of bottom soil of nursery ponds were inversely significant (P < 0.05) in nature. Dissolved O2 and phosphate P of water had almost direct correlations with bottom soil properties of nursery ponds where dissolved O2 had significant (P < 0.05) correlation with pH of bottom soil.